Evaluation of the anti-colagenase activity of the latex of Croton lechleri - Obando, Lucio (2020)
In recent years, interest in the elimination of “wrinkles” has motivated the cosmetic industry to carry out research based on medicinal plants that contain antioxidant, anticolagenase and antielastase properties. Croton lechleri “blood of degree” is a plant that is known for its healing property; However, this activity may give you the anti-collagenase property, which you can evaluate by several methods. The objective of this work is to evaluate the anti-collagenase activity of Croton lechleri latex “blood grade”. To carry out this evaluation, the Thing methodology was used, which is carried out, comparing the activity (absosbances) generated by the epigallocatechin pattern with the Croton lechleri latex samples at the following concentrations: 125, 250, 500 and 1000ug / mL at the end of this method, it was found that Croton lechleri latex showed anti-collagenase activity of IC50 = 908.02 µg / mL, with respect to the positive control epigallocatechin gallate (EGCG) of IC50 = 1892.03 µg / mL). This concludes that Croton lechleri latex manifests anticolagenase activity with greater inhibition potential than the positive control of EGCG.